SIMULATION OF INERTIAL NAVIGATION SYSTEM ERRORS AT AERIAL PHOTOGRAPHY FROM UAV - R. Shults (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2017)
The problem of accuracy determination of the UAV position using INS at aerial photography can be resolved in two different ways: modelling of measurement errors or in-field calibration for INS. The paper presents the results of INS errors research by mathematical modelling. In paper were considered the following steps: developing of INS computer model; carrying out INS simulation; using reference data without errors, estimation of errors and their influence on maps creation accuracy by UAV data. It must be remembered that the values of orientation angles and the coordinates of the projection centre may change abruptly due to the influence of the atmosphere (different air density, wind, etc.). Therefore, the mathematical model of the INS was constructed taking into account the use of different models of wind gusts. For simulation were used typical characteristics of micro electromechanical (MEMS) INS and parameters of standard atmosphere. According to the simulation established domination of INS systematic errors that accumulate during the execution of photographing and require compensation mechanism, especially for orientation angles. MEMS INS have a high level of noise at the system input. Thanks to the developed model, we are able to investigate separately the impact of noise in the absence of systematic errors. According to the research was found that on the interval of observations in 5 seconds the impact of random and systematic component is almost the same. The developed model of INS errors studies was implemented in Matlab software environment and without problems can be improved and enhanced with new blocks.